Di-n-butylammonium 2-(3,5-di-tert-butyl-4-hydroxybenzylsulfanyl)nicotinate - Ariffin, Azhar; Ng, S.W.; Mansor, S.; Yehye, W.A.; Rahman, N.A. (International Union of Crystallography, 2008)
The asymmetric unit of the title compound, C(8)H(20)N(+)center dot C(21)H(26)NO(3)S(-), contains two indpendent ion pairs which are disposed about a psuedo-inversion center, generating an ammonium-carboxylate N-H center dot center dot center dot O hydrogen-bonded four-component cluster. In the crystal structure, adjacent clusters are linked by hydroxy-carboxylate O-H center dot center dot center dot O hydrogen bonds, forming a chain.